Malnutrition in real-world patients hospitalized for heart failure with preserved ejection fraction and its potential impact on generalizability of EMPEROR-Preserved trial. (1st January 2023) - Takeuchi, Shinsuke; Kohno, Takashi; Goda, Ayumi; Shiraishi, Yasuyuki; Saji, Mike; Nagatomo, Yuji; Tanaka, Toshikazu D.; Takei, Makoto; Nakano, Shintaro; Soejima, Kyoko; Kohsaka, Shun; Yoshikawa, Tsutomu; et al.
Abstract: Background: Despite the benefits of the sodium-glucose cotransporter 2 inhibitor (SGLT2i) empagliflozin, its suitability for patients with heart failure (HF) in the real-world setting remains unclear. Considering the unique pharmacological profile of SGLT2i (e.g., glucose excretion leading to calorie loss) and increasingly aging patients with HF, applicability of trials' finding in patients with malnutrition is important. Methods: We examined 1633 consecutive patients with a preserved left ventricular ejection fraction (LVEF; >40%) enrolled in a multicenter-based acute HF registry. After applying the EMPEROR-Preserved eligibility criteria, we compared the baseline characteristics of trial-eligible and actual trial participants, and patients with and without malnutrition among the trial-eligible group. Malnutrition was assessed by the geriatric nutritional risk index (GNRI). The trial-eligible patients were divided into high (GNRI≥92) and low (GNRI<92) nutritional groups, and a composite endpoint comprising all-cause death and HF rehospitalization was evaluated. Results: Majority (70.2%) of the analyzed patients were eligible for the EMPEROR-Preserved trial (age: 77 ± 12 years and body mass index [BMI]: 22.0 ± 4.1 kg/m 2 ), but were older and had lower BMIs than the actual trial participants. Notably, 51.9% of the eligible patients were at high risk for malnutrition and had a higher rate of the composite endpoint than non-malnourished counterparts (HR 1.27, 95%CI 1.04–1.56, P  = 0.020). The difference in outcomes was predominantly due to mortality from non-cardiac causes. Conclusions: Mostly patients with HF in a real-world setting met the EMPEROR-Preserved criteria; however, approximately half were at high risk for malnutrition with poorer outcomes owing to non-cardiac-related causes. Graphical abstract: Unlabelled Image Highlights: ≈70% of real-world patients with HF met the EMPEROR-Preserved criteria. The trial-eligible patients were older with lower BMI than the actual trial patients. Malnutrition was common in the trial-eligible patients. Malnutrition was associated with worse clinical outcomes in trial-eligible cases. The non-cardiac mortality rate was higher in patients at high risk of malnutrition.